Improvement of Cecal Commensal Microbiome Following the Insect Additive into Chicken Diet - Józefiak, Agata (Animals (Basel), 2020)
SIMPLE SUMMARY: Throughout their lifecycle, insects can be a rich source of many valuable nutrients and biologically active components. It was demonstrated that the additive of Tenebrio molitor (TM) and Zophobas morio (ZM) into broiler chicken diet can have a positive effect on their growth parameters as well as some microbial composition in the gastrointestinal tract (GIT). Therefore, the present study evaluated the effect of diet with the addition of Tenebrio molitor and Zophobas morio (0.2 and 0.3%) on the cecal microbiome in broilers. The addition of 0.2% ZM compared to the negative control (NC) group resulted in an increase in relative abundance of the Actinobacteria, including the family Bifidobacteriaceae, with the highest relative abundance of genus Bifidobacterium pseudolongum. The addition of 0.2% ZM resulted in an increase in the number of Lactobacillus agilis. The highest relative abundance of the family Ruminococcaceae was observed in the 0.2 TM group together with Lactobacillus reuteri but with no significant differences. Furthermore, a significant level of Clostridia was observed in the 0.2 TM group. A relatively small addition of Tenebrio molitor and Zophobas morio to broiler diet can modulate commensal and probiotic microbiome composition in the cecum and increase the relative abundance of positive bacteria to have a positive impact on gut health of broilers. ABSTRACT: Gastrointestinal microbiota play an important role in regulating the metabolic processes of animals and humans. A properly balanced cecal microbiota modulates growth parameters and the risk of infections. The study examined the effect of the addition of 0.2% and 0.3% of Tenebrio molitor and Zophobas morio on cecal microbiome of broilers. The material was the cecum digesta. The obtained DNA was analyzed using 16S rRNA next generation sequencing. The results of the study show that the addition of a relatively small amount of Z. morio and T. molitor modulates the broiler cecum microbiome composition. The most positive effect on cecal microbiota was recorded in the 0.2% Z. morio diet. A significant increase in the relative amount of genus Lactobacillus, represented by the species Lactobacillus agilis and the amount of bacteria in the Clostridia class, was observed. Moreover, the addition of 0.2% ZM resulted in a significant increase of relative abundance of the family Bifidobacteriaceae with the highest relative abundance of genus Bifidobacterium pseudolongum. The obtained results indicate that the addition of a relatively small amount of insect meal in broiler diet stimulates colonization by probiotic and commensal bacteria, which may act as barriers against infection by pathogenic bacteria.